Primary end-point times, functional outcome and adverse event profile after acute ischaemic stroke - Ali, Myzoon; Sacco, R. L.; Lees, K. R.; Hacke, Werner; Hennerici, Michael G. (International journal of stroke, 2009)
BackgroundPoststroke complications such as pulmonary embolism, deep vein thrombosis and pneumonia can impact outcome by causing deterioration in general health, delaying or preventing rehabilitation. While stroke carries a direct risk of complications, some events may be unrelated to index stroke severity and could confound outcome. We examined whether the presence of complications ?unrelated? to index stroke at later time-points could confound outcome, and if this could be minimised through altering study end-points.MethodsWe analysed 531 placebo-treated patients from the Virtual International Stroke Trials Archive who had experienced an acute ischaemic stroke and at least one poststroke complication during the 90-day follow-up period. We categorised complications into those deemed ?related? or ?unrelated? to index stroke severity. We examined modified Rankin Scale at 30 and 90 days, stratified by type of complication and assessed the impact of eliminating ?unrelated? complications on functional outcome (modified Rankin Scale) at 30 and 90 days using logistic regression (accounting for age and baseline National Institutes of Health Stroke Scale).ResultsThe majority of complications in the early acute period after index stroke were ?stroke related? (30·2%). Patients did not have a better modified Rankin Scale profile at 30 days when compared with 90 days, regardless of the type of complications experienced. The absence of ?stroke unrelated? complications was associated with a worse outcome at 30 days [P = 0·04, adjusted odds ratio for good functional outcome = 0·54, 95% confidence interval (0·3, 0·96)], and had no significant effect on outcome at 90 days.ConclusionsWe identified complications, which we deemed not to have occurred as a direct consequence of index stroke, but found that the absence of these events did not beneficially alter outcome at either short-term (30 days) or long-term (90 days) follow-up periods. Our analyses did not support the shortening of trial follow-up periods with the aim of minimising the risk of stroke-unrelated complications.
Gesehen am 17.03.2021
VISTA Steering committee: Lees K.R. (chair), Bath P M.W., Bluhmki E., Claesson L., Curram J., Davis S.M., Diener H.C., Donnan G.A., Fisher M., Gregson B.A., Grotta J., Hacke W., Hennerici M.G., Hommel M., Kaste M., Lyden P., Marler J., Muir K., Sacco R.L., Shuaib A., Teal P., Wahlgren N.G., Warach S. and Weimar C